Analysis Of The Application Of Fruit And Vegetable Storage At The Grand Istana Rama Hotel Bali - Baskara, Wahyu Padma; Eucharisto, Thomas More Elang; Wasistha, I Ketut Krisna Drana; Soimun, Ahmad; Sari, Putu Mia Arista (Politeknik Internasional Bali, 2023)
Hotel operations are not only about room rentals. Customer satisfaction with the services provided is also assessed from the cuisine served at the hotel restaurant. Fulfilment of customer satisfaction, especially in the food sector, is supported by qualified storage infrastructure. This study aims to determine the important role of cold storage in fruit and vegetable storage at Grand Istana Rama Hotel Bali. Data collection techniques using the interview method of resource persons, namely food management and beverages department. In addition, research is carried out through direct observation of activities, and literature and literature studies as secondary data. Data analysis is carried out in a qualitative descriptive manner by summarizing, describing, and analysing the condition of the situation at the hotel. Based on the results of the study, it was found that cold storage is considered very important in restaurant operations, especially when food ingredients arrive at the hotel but are not immediately processed. Cold storage has benefits for maintaining the quality and freshness of fruit raw materials, avoiding viral and bacterial contamination, and reducing the use of preservatives in fruits and vegetables. This research will provide information related to the process of storing fruits and vegetables using cold storage to maintain freshness.